Effect of adrenocorticotropic hormone infusion on circulating sclerostin levels. Issue 12 (14th December 2021) - Zaheer, Sarah; Meyer, Kayla; Easly, Rebecca; Bayomy, Omar; Leung, Janet; Koefoed, Andrew W; Heydarpour, Mahyar; Freeman, Roy; Adler, Gail K
Abstract : Glucocorticoid use is the most common cause of secondary osteoporosis. Poor skeletal health related to glucocorticoid use is thought to involve inhibition of the Wnt/β-catenin signaling pathway, a key pathway in osteoblastogenesis. Sclerostin, a peptide produced primarily by osteocytes, is an antagonist of the Wnt/β-catenin signaling pathway, raising the possibility that sclerostin is involved in glucocorticoids' adverse effects on bone. The aim of this study was to determine whether an acute infusion of cosyntropin (i.e. ACTH(1–24)), which increases endogenous cortisol, increases serum sclerostin levels as compared to a placebo infusion. This study was performed using blood samples obtained from a previously published, double-blind, placebo-controlled, randomized, cross-over study among healthy men and women who received infusions of placebo or cosyntropin after being supine and fasted overnight (ClinicalTrials.gov NCT02339506). A total of 17 participants were analyzed. There was a strong correlation (R 2  = 0.65, P < 0.0001) between the two baseline sclerostin measurements measured at the start of each visit, and men had a significantly higher average baseline sclerostin compared to women. As anticipated, cosyntropin significantly increased serum cortisol levels, whereas cortisol levels fell during placebo infusion, consistent with the diurnal variation in cortisol. There was no significant effect of cosyntropin as compared to placebo infusions on serum sclerostin over 6–24 h ( P  = 0.10). In conclusion, this randomized, placebo-controlled study was unable to detect a significant effect of a cosyntropin infusion on serum sclerostin levels in healthy men and women.